The Reciprocal Relationship Between Sexual Arousal and Disgust as Evidenced in Automatic Approach-Avoidance Behavior. Issue 3 (23rd March 2020) - Hinzmann, Jessica; Borg, Charmaine; Verwoerd, Johan R. L.; de Jong, Peter J.
Abstract : Sexual encounters imply exposure to stimuli that in other contexts typically elicit disgust-induced avoidance. To explain why people nevertheless tend to show sexual approach, it has been proposed that heightened sexual arousal may temporarily inhibit disgust. In line with this, studies have found that sexually aroused individuals showed heightened willingness to approach disgusting stimuli. Because automatic processes are critically involved in sexual behaviors, we examined whether the impact of sexual arousal extends to automatic responses to disgust-elicitors. To test the proposed reciprocal relationship between sex and disgust, we also investigated whether disgust reduces automatic sexual approach. In Study 1, 116 female participants ( M = age 19.53) were assigned to a sexual arousal or control condition and performed a speeded approach-avoidance task to assess automatic responses to disgusting stimuli. In Study 2, 174 female participants ( M = age 22.14) were assigned to a disgust, sexual arousal, or control condition and performed an approach-avoidance task involving both sex and disgust-relevant stimuli. Sexual arousal did not affect automatic responses to disgusting stimuli, and disgust did not influence automatic responses towards sexual stimuli. The reciprocal relationship between sexual arousal and disgust that was previously found for controllable responses did not extend to automatic responses.